Police programmes that seek to increase community connectedness for reducing violent extremism behaviour, attitudes and beliefs - Mazerolle, Lorraine (Campbell Systematic Reviews, 2020)
The review aimed to systematically examine whether or not police programmes that seek to promote community connectedness are effective in reducing violent extremist behaviours, attitudes and beliefs. The review also sought to identify whether effectiveness varied by the intervention type and location.